1997
DOI: 10.1159/000011841
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up and Prognostic Factors in Ewing’s Sarcoma

Abstract: The records of 116 patients from a single center (1970–1993) with newly diagnosed Ewing’s sarcoma or primitive neuroectodermal tumor were reviewed retrospectively. The aim of this study was to ascertain the impact of pretreatment variables on disease-free survival. Median age was 14 years (range 1–34). Twenty patients presented with metastatic disease. Treatment consisted of systemic multiagent chemotherapy plus local irradiation (39%), wide resection (22%), or both (35%). Median potential follow-up was 10.7 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(9 citation statements)
references
References 22 publications
0
7
0
2
Order By: Relevance
“…It was concluded that presurgical serum albumin levels can be used to evaluate the success of randomization of clinical trials for glioblastoma multiforme therapies [91]. Another showed that raised serum LDH levels, hypoalbuminemia and distant metastases at diagnosis were independent adverse prognostic factors in 116 patients with Ewing's sarcoma [92]. A study done with an objective of determining prognostic factors for survival in renal cancer patients found the following variables to be statistically significant at the univariate analysis (p < 0.01): disease free interval (DFI), PS, stage at diagnosis, grading, nephrectomy, sites of metastases, blood hemoglobin, serum albumin, calcium, LDH, ALP [93].…”
Section: Resultsmentioning
confidence: 99%
“…It was concluded that presurgical serum albumin levels can be used to evaluate the success of randomization of clinical trials for glioblastoma multiforme therapies [91]. Another showed that raised serum LDH levels, hypoalbuminemia and distant metastases at diagnosis were independent adverse prognostic factors in 116 patients with Ewing's sarcoma [92]. A study done with an objective of determining prognostic factors for survival in renal cancer patients found the following variables to be statistically significant at the univariate analysis (p < 0.01): disease free interval (DFI), PS, stage at diagnosis, grading, nephrectomy, sites of metastases, blood hemoglobin, serum albumin, calcium, LDH, ALP [93].…”
Section: Resultsmentioning
confidence: 99%
“…In bone sarcomas, CRP, albumin level [24], [25], and lymphocyte and/or neutrophils [26], [27] were shown to be of prognostic value. These few studies, however, suffer from different problems such as not correcting for confounders and the lack of pretreatment values or hazard ratio levels.…”
Section: Discussionmentioning
confidence: 99%
“…[23] Cases of kidney, myocardium, rectum, ovary, retroperitoneum, and bladder involvement have been reported. [16101214]. …”
Section: Discussionmentioning
confidence: 99%